Academic Expectations of MARA Stakeholders on the Ulul Albab Curriculum at a MARA Junior Science College / Umi Kalthom Abdul Manaf...[et al.] - Abdul Manaf, Umi Kalthom; Alias, Nurul Fitriah; Nor Azman, Ady Hameme (Universiti Teknologi MARA, Kedah, 2015)
Ulul Albab is an educational programme of integration between the existing programmes in the MARA Junior Science College (MRSM) with the religious school programme including Tahfiz Al-Quran. The MRSM Ulul Albab education programme is designed to produce professional experts, entrepreneurs and technocrats that are well versed in the field of religion that is based on Al-Quran and Sunnah known as the Ulul Albab generation. This study aims to explore stakeholders' expectations on the Ulul Albab programme in MRSM Kota Putra, Besut Terengganu towards students' academic excellence. The methodology used was qualitative in nature in the form of semi-structured interviews conducted with the four MARA stakeholders. Regarding the validity and reliability of data, several techniques were employed such as member checking, rich thick description, clarification of researcher bias, peer review and debriefing, and external audit. The findings from this study indicate that the stakeholders hope that Ulul Albab programme will be able to produce academically excellent students who possess creative and critical thinking skills. Apart from that, the stakeholders also expressed the need towards education that is balanced in both duniawi (world) and ukhrawi (hereafter).